USER EXPERIENCE ANSWER SYSTEM AUTOMATICALLY WITH USER CENTERED DESIGN AND USER EXPERIENCE QUESTIONNAIRE-SHORT - Sophia Nouriska; Meida Cahyo Untoro; Aidil Afriansyah; Mugi Praseptiawan; Winda Yulita; Ilham Firman Ashari (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2023)
The interface of the automatic answer assessment system is plagued by several issues, including an unfamiliar layout, unresponsive design, inconsistency in elements, and a lack of clarity in presenting information. These problems significantly hinder the overall user experience. As a result, this study aimed to address these challenges by designing a user-centered experience for the automatic answer assessment system, using a high-fidelity prototype tailored to meet user needs. The user-centered design method involved four crucial stages: Specify The Context Of Use, Specify Requirements, Create Designs, and Evaluate Designs. Through rigorous usability testing with teachers, the design achieved an impressive effectiveness rating of 90%, firmly establishing it as a "very effective" solution. Additionally, it demonstrated high efficiency with a value of 0.01307 goals/sec, and teachers expressed positive feedback, confirming the satisfaction and usability of the new interface. Similarly, students' usability testing yielded noteworthy results, with a 90% effectiveness rating, also classified as "very effective." The interface showcased a high level of efficiency, with a value of 0.0849 goals/sec. While the satisfaction value fell below the PSSUQ norm, students still found the interface to be user-friendly and satisfactory. Furthermore, the user experience testing, utilizing the UEQ-S, provided valuable insights. For teachers, the pragmatic aspect scored 1.85, the hedonic aspect scored 2.33, and the overall aspect received a commendable score of 2.09, all of which fell within the excellent category on benchmarks. Similarly, students' ratings were highly positive, with scores of 2.14 for both pragmatic and hedonic aspects, and an overall score of 2.14, signifying an excellent user experience.The retrospective think-aloud validation test reaffirmed the positive response from prospective users. Overall, this research, employing a user-centered design approach, successfully delivered a highly satisfactory and effective user experience for both teachers and students using the automatic answer assessment system.